A Systematic Review of SBRT Boost for Cervical Cancer Patients Who Cannot Benefit from Brachytherapy - Iozsef Gazsi; Loredana G. Marcu (Current Oncology)
Stereotactic body radiation therapy has emerged as a promising alternative to brachytherapy, delivering high doses to tumors with precision while sparing surrounding organs. This systematic review evaluates the role of SBRT as a boost for patients who are ineligible for brachytherapy. A total of 17 studies, involving 288 patients, were analyzed, focusing on dosimetric parameters and toxicity. The radiation regimens varied in dose and fractionation schedules, with external beam doses ranging from 44 to 61.6 Gy, and SBRT boost doses ranging from 5 to 30 Gy. The total EQD2 doses were between 50.5 and 92.4 Gy. The results indicate adequate tumor control with SBRT, with local control rates ranging from 57% to 95.5%. The acute genitourinary and gastrointestinal toxicities were mostly grade 1 or 2, while late toxicities were less common. The overall survival rates varied between 34% and 96%. These results suggest that SBRT boost offers a viable option for cervical cancer patients ineligible for brachytherapy, with acceptable toxicity and promising survival outcomes. Nevertheless, the scarcity of data, which mainly originate from small studies with patients having varied stages of disease, as well as the lack of long-term follow up with SBRT, should encourage clinicians to utilize brachytherapy whenever suitable as a boost in these patient cohorts.